The effect of high-intensity interval training on triglyceride levels in obese adolescents - Prasetyo, yona bayu; Hadiono; Andryas yuniarto; Vega Mareta sceisarriya; Achmad furqon Bildhonny; Tiassari Janjang Suminar (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study aims to analyze the effect of HIIT training on triglyceride levels in obese adolescents. This study used an experimental method with a pretest–posttest control group design. A total of 32 adolescents with type I obesity (BMI >31–38 kg/m²) were divided into an experimental group and a control group. The experimental group underwent HIIT training with a ratio of 10 seconds of work and 20 seconds of rest for six weeks with a frequency of three times per week, while the control group did not receive structured training. Blood triglyceride levels were measured using the SD BIOSENSOR LipidoCare Analyzer before and after the intervention. Data analysis was performed using paired sample t-tests and independent sample t-tests with a significance level of 0.05. The results showed that HIIT significantly reduced triglyceride levels from 351.1±6.9 mg/dL to 140.1±2.2 mg/dL (p<0.001). In addition, body mass index also decreased significantly from 34.3±0.4 kg/m² to 30.5±0.15 kg/m² (p=0.012). The greater decrease in triglycerides compared to BMI indicates that metabolic improvement can occur more quickly than anthropometric changes. It is concluded that HIIT exercise is effective in lowering triglyceride levels and improving metabolic health in obese adolescents. HIIT can be recommended as an efficient and applicable exercise strategy in efforts to prevent cardiometabolic risks from adolescence.